ADAPTASI PERUBAHAN RUANG BERHUNI UNIT RUMAH TINGGAL PADA CLUSTER WINDSOR PERUMAHAN ROYAL RESIDENCE SURABAYA - Intan Cezarayu Tahalele; Iwan Wibisono (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Housing is a collection of dwellings, that have the same size, typical, facilities, color with the same interior between one house and another in a block or cluster. One of the mosgt important isgsues in the development of the housing service provider industry is the level of occupant or consumer satissfaction. Occupants or consumers have different needs gin each residence so research is neededd to find out the leveel of satisfaction of residents and what changes the residence in accordance with the needs and desires of residents. The preferred object in study is a residential unit in the Cluster Windsor Royal Residence Surabaya, as manyas 67 houses with a descriptive qualitative method. The results of this study contain suggestions for developers to find out the level of consumer or occupant satisfaction and modification of residential elements that can be used in future housing developments.